Associations of endogenous 17-β-estradiol with theta amplitude and performance in semantic categorization in young women - Brötzner, C.P. (Neuroscience, 2015)
In semantic categorization processes, individuals form a relation between perceived or imagined objects and knowledge about these objects. In the present semantic categorization study, we correlated endogenous 17-β-estradiol levels (E2) with performance as well as amplitude of theta oscillations in young women (age 23.1 ± 3.4 years). The semantic categorization task consisted of nouns representing either living or non-living items. Each item was characterized either by many or by few features. We identified parameters associated or not associated with menstrual cycle phases. Irrespective of the menstrual cycle phase, women (1) responded faster to living items as well as to nouns characterized by many features compared to non-living items and items characterized by few features, (2) showed higher accuracy to non-living items and items having many features, and (3) showed negative correlation between response time (RT) and theta amplitude. RT, accuracy and post-stimulus theta amplitude were not statistically significantly different among early follicular, late follicular or luteal women. In early follicular but not in late follicular or luteal women, we observed (1) a positive correlation between E2 and latency in RT, (2) a negative correlation between E2 and accuracy, and (3) a negative correlation between E2 and post-stimulus theta amplitude. A mosaic of menstrual cycle phase-dependent and -independent associations may indicate that a similar performance in each menstrual cycle phase is related to different modulation of synaptic activity by hormones.